Сountry’s energy policy in context of the world economy’s ecologization - Kuznietsova, Kateryna; Chenusha, Oleksandr (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Міжнародні відносини, економіка, країнознавство, туризм, 2021)
Acceleration of economic processes in the world necessitates a rapid response to change, which when considering the transition to greening the economy should be reflected in the country’s energy policy. The object of research in this article is the fuel and energy sector of the world, and the subject of research - energy policy. The purpose of the scientific article is to assess the development trends of the fuel and energy complex of Ukraine in modern conditions and identify key trends in its development; determination of the main directions of energy policy and diplomacy of the country in the conditions of world economy’s greening. Research methods used: method of analysis, synthesis, systematization, comparison, abstract-logical method, statistical methods of research of economic processes. The main results were: determination of fuel reserves of Ukraine and its natural resource potential; analysis of final energy consumption and identification of trends in the level of energy intensity of GDP; assessment of the electricity generation structure in Ukraine and changes in the share of renewable energy sources; establishing ways to encourage greening of industry and prospects for implementing an environmental approach; determining the directions of energy policy and diplomacy of Ukraine in the context of the world economy’s greening. Thus, in modern business conditions, an important condition for the effective functioning of any economic system has become flexibility and the ability to quickly adapt to market conditions. Therefore, the development of an extensive system of tasks of the state’s energy strategy with those developed in accordance with the realities of a particular management system is the key to successful energy policy. And establishing cooperation in the energy sector will allow us to adopt the experience of developed countries and integrate into the European and global energy community. The ecological vector of energy systems development has been an integral trend for many years and will soon become a constant for the effective development of the country. Therefore, the implementation of preventive measures to green economy is an urgent issue of Ukraine's energy policy.